2021
DOI: 10.1038/s41598-021-98280-6
|View full text |Cite
|
Sign up to set email alerts
|

Covalent functionalization of polypropylene filters with diazirine–photosensitizer conjugates producing visible light driven virus inactivating materials

Abstract: The SARS-CoV-2 pandemic has highlighted the weaknesses of relying on single-use mask and respirator personal protective equipment (PPE) and the global supply chain that supports this market. There have been no major innovations in filter technology for PPE in the past two decades. Non-woven textiles used for filtering PPE are single-use products in the healthcare environment; use and protection is focused on preventing infection from airborne or aerosolized pathogens such as Influenza A virus or SARS-CoV-2. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“… 12 , 13 Additionally, Menon et al demonstrated that post-functionalization of PP masks can result in effective sterilization through the use of zinc porphyrin photosensitizers for enhancing the ability of the masks to protect against influenza pathogens. 14 Alternatively, masks can be collected and recycled through several processing steps, such as granulation and pelletization. While such mechanical recycling methods have been established in industry, they often result in downgraded material properties and a less valuable product due to increased yellowness and reduced melt viscosity from possible chain scission under high shear.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Additionally, Menon et al demonstrated that post-functionalization of PP masks can result in effective sterilization through the use of zinc porphyrin photosensitizers for enhancing the ability of the masks to protect against influenza pathogens. 14 Alternatively, masks can be collected and recycled through several processing steps, such as granulation and pelletization. While such mechanical recycling methods have been established in industry, they often result in downgraded material properties and a less valuable product due to increased yellowness and reduced melt viscosity from possible chain scission under high shear.…”
Section: Introductionmentioning
confidence: 99%
“…19 Diazirine reagents can also add functionality to commodity polymers; 20 for example porphyrin conjugate 8 can be used to generate antiviral coatings on woven polypropylene filter material. 21 The aryl diazirines discussed above range from moderately electron rich (3) to moderately electron poor (1 and 6), with the majority being electron neutral. This raises an important but unaddressed question: what kind of aryl diazirine is preferred in order to maximize the efficacy of polymer crosslinking?…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of a tetra-substituted diazirine porphyrin covalently bonded to nonwoven melt-blown polypropylene textiles was demonstrated by our group to be efficient for virus inactivation. 45 Here, we explore the use of the diazirine photosensitizer for greener and potentially more effective prevention and treatment of bacteria on polyethylene terephthalate (PET).…”
Section: Introductionmentioning
confidence: 99%